Multigenerational Study of Chemically Induced Cytotoxicity and Proliferation in Cultures of Human Proximal Tubular Cells - Lash, Lawrence H. (Int J Mol Sci, 2014)
Primary cultures of human proximal tubular (hPT) cells are a useful experimental model to study transport, metabolism, cytotoxicity, and effects on gene expression of a diverse array of drugs and environmental chemicals because they are derived directly from the in vivo human kidney. To extend the model to investigate longer-term processes, primary cultures (P0) were passaged for up to four generations (P1–P4). hPT cells retained epithelial morphology and stained positively for cytokeratins through P4, although cell growth and proliferation successively slowed with each passage. Necrotic cell death due to the model oxidants tert-butyl hydroperoxide (tBH) and methyl vinyl ketone (MVK) increased with increasing passage number, whereas that due to the selective nephrotoxicant S-(1,2-dichlorovinyl)-l-cysteine (DCVC) was modest and did not change with passage number. Mitochondrial activity was lower in P2–P4 cells than in either P0 or P1 cells. P1 and P2 cells were most sensitive to DCVC-induced apoptosis. DCVC also increased cell proliferation most prominently in P1 and P2 cells. Modest differences with respect to passage number and response to DCVC exposure were observed in expression of three key proteins (Hsp27, GADD153, p53) involved in stress response. Hence, although there are some modest differences in function with passage, these results support the use of multiple generations of hPT cells as an experimental model.